Neologisms in the poetic series Dark Vision and Worlds of Enlightenment by Daniil Andreev - Banasiak, Daniel (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The article discusses neologisms in the poetic series Dark Vision and Worlds of Enlightenment by Daniil Andreev. Andreev creates ontologically complex worlds in his creative attempts. New words are needed to describe these unreal places. He creates such words inspired by the philosophy of Ramakrishna, Ramanuja, and Patanjali and boldly drawing on the culture of the Middle East. The neologisms do not only emphasize the author’s erudition, but above all, they bring new meanings to his poetic universe.